In sickness and in health? Comorbidity in older couples - Cara L. Booker; Stephen Pudney (University of Essex, Institute for Social and Economic Research (ISER), 2013)
We investigate the nature and origin of comorbidity, defined as the tendency of members of marital couples to display correlated patterns of ill-health in later life. In the absence of long-term prospective data on couples, we use long-range recall data from the pan-European SHARELife survey and estimate a latent variable model of the health states of marital partners in childhood, early adulthood and late adulthood. We find strong persistence in health states and a strong comorbidity correlation, attributable almost equally to homogamy in relation to early health and common factors operating within marriage.
Keywords: I12; J13; 330; Health; disability; lifecourse; homogamy; SHARE